Investigation of refraction effects for small GPS networks - Christiaans, Johan (School of Architecture, Planning and Geomatics, 2016)
Using observations from the Global Positioning System (GPS) satellites to determine a three dimensional (3-D) geodetic control network are considered. The repeatability of individual baselines and 3-D vector closures are examined, in order to investigate refraction effects on GPS networks. The effect on GPS baselines of a height bias in the reference point's coordinates is also investigated. A least squares adjustment program is developed and used to obtain a single consistent set of 3-D coordinates for the Tygerberg Test Network (TTN). The results of two GPS processing packages are compared by means of a conformal transformation. It is concluded that single frequency measurements produce better results than the ionospheric free observable on short baselines. Furthermore, a standard atmospheric model shows an improvement over the Marini model to account for tropospheric refraction.